Ivacaftor attenuates gentamicin-induced ototoxicity through the CFTR-Nrf2-HO1/NQO1 pathway - Rui Hu; Fan Wu; Yi-Qing Zheng (Taylor & Francis Group, 2024)
ABSTRACTObjectives Gentamicin is one of the most common ototoxic drugs that can lower patients' quality of life. Oxidative stress is a key factors inducing sensory hair cell death during gentamicin administration. So far, there are no effective drugs to prevent or treat gentamicin- induced hearing loss. A recent study found cystic fibrosis transmembrane conductance regulator (CFTR) as a new target to modulate cellular oxidative balance. The objective of this study was to estimate the effect of the CFTR activator ivacaftor on gentamicin-induced ototoxicity and determine its mechanism.Methods The hair cell count was analyzed by Myosin 7a staining. Apoptosis was analyzed by TUNEL Apoptosis Kit. Cellular reactive oxygen species (ROS) level was detected by DCFH-DA probes. The Nrf2 related proteins expression levels were analyzed by western blot.Results An in vitro cochlear explant model showed that gentamicin caused ROS accumulation in sensory hair cells and induced apoptosis, and this effect was alleviated by pretreatment with ivacaftor. Western blotting showed that ivacaftor administration markedly increased the protein expression of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO1), and NAD(P)H:quinone oxidoreductase 1 (NQO1). The protective effect of ivacaftor was abolished by the Nrf2 inhibitor ML385.Discussion Our results indicate the protective role of the CFTR-Nrf2-HO1/NQO1 pathway in gentamicin-induced ototoxicity. Ivacaftor may be repositioned or repurposed towards aminoglycosides-induced hearing loss.